2020
DOI: 10.21203/rs-42600/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auxora Versus Standard of Care For The Treatment of Severe or Critical COVID-19 Pneumonia: Results From A Randomized Controlled Trial

Abstract: BACKGROUND: Calcium release-activated calcium (CRAC) channel inhibitors stabilize the pulmonary endothelium and block proinflammatory cytokine release, potentially mitigating respiratory complications observed in patients with COVID-19. This study aimed to investigate the safety and efficacy of Auxora, a novel, intravenously administered CRAC channel inhibitor, in adults with severe or critical COVID-19 pneumonia METHODS: A randomized, controlled, open-label study of Auxora was conducted in adults with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The remaining trial comparisons included: favipiravir versus umifenovir [33]; umifenovir versus lopinavir-ritonavir [40]; umifenovir versus standard care [40]; novaferon versus novaferon plus lopinavir-ritonavir [45]; novaferon plus lopinavir-ritonavir versus lopinavir-ritonavir [45]; novaferon versus lopinavir-ritonavir [45]; alpha lipotic acid versus placebo [46]; baloxavir marboxil versus favipavir [41]; baloxavir marboxil versus standard care [41]; triple combination of interferon beta-1b plus lopinavir-ritonavir plus ribavirin versus lopinavir-ritonavir [38]; remdesivir for 5 days versus remdesivir for 10 days [37]; high-flow nasal oxygenation versus standard bag-valve oxygenation [44]; hydroxychloroquine versus chloroquine [48]; chloroquine versus standard care [48]; high dosage chloroquine diphosphate versus low dosage chloroquine diphosphate [50]; hydroxychloroquine plus azithromycin versus standard care [54]; triple combination of darunavir plus cobicistat plus interferon alpha-2b versus interferon alpha-2b [117]; lopinavir-ritonavir plus interferon alpha versus ribavirin plus interferon alpha [61]; ribavirin plus lopinavir-ritonavir plus interferon alpha versus ribavirin plus interferon alpha [61]; ribavirin plus lopinavir-ritonavir plus interferon alpha versus lopinavir-ritonavir plus interferon alpha [61]; lincomycin versus azithromycin [62];, 99-mTc-methyl diphosphonate (99mTc-MDP) injection versus standard care [63]; interferon alpha-2b plus interferon gamma versus interferon alpha-2b [64]; telmisartan versus standard care [66]; avifavir 1800/800 versus avifavir 1600/600 [67]; dexamethasone plus aprepitant versus dexamethasone [69]; anti-C5a antibody versus standard care [70]; azvudine versus standard care [73]; human plasma-derived C1 esterase/kallikrein inhibitor versus standard care [72]; icatibant acetate versus standard care [72]; icatibant acetate versus human plasma-derived C1 esterase/kallikrein inhibitor [72]; pulmonary rehabilitation program versus isolation at home [71]; auxora (calcium release-activated calcium channel inhibitors) versus standard care [74]; umbilical cord stem cell infusion versus standard care [75]; vitamin C versus placebo [76]; sofosbuvir plus daclatasvir versus standard care [80]; sofosbuvir plus daclatasvir plus ribavirin versus hydroxychloroquine plus lopinavir-ritonavir with or without ribavirin [79]; interferon beta-1b versus standard care [81]; calcifediol versus standard care [84]; recombinant human granulocyte colony–stimulating factor versus standard care [85]; intravenous and/or nebulized electrolyzed saline w...…”
Section: Resultsmentioning
confidence: 99%
“…The remaining trial comparisons included: favipiravir versus umifenovir [33]; umifenovir versus lopinavir-ritonavir [40]; umifenovir versus standard care [40]; novaferon versus novaferon plus lopinavir-ritonavir [45]; novaferon plus lopinavir-ritonavir versus lopinavir-ritonavir [45]; novaferon versus lopinavir-ritonavir [45]; alpha lipotic acid versus placebo [46]; baloxavir marboxil versus favipavir [41]; baloxavir marboxil versus standard care [41]; triple combination of interferon beta-1b plus lopinavir-ritonavir plus ribavirin versus lopinavir-ritonavir [38]; remdesivir for 5 days versus remdesivir for 10 days [37]; high-flow nasal oxygenation versus standard bag-valve oxygenation [44]; hydroxychloroquine versus chloroquine [48]; chloroquine versus standard care [48]; high dosage chloroquine diphosphate versus low dosage chloroquine diphosphate [50]; hydroxychloroquine plus azithromycin versus standard care [54]; triple combination of darunavir plus cobicistat plus interferon alpha-2b versus interferon alpha-2b [117]; lopinavir-ritonavir plus interferon alpha versus ribavirin plus interferon alpha [61]; ribavirin plus lopinavir-ritonavir plus interferon alpha versus ribavirin plus interferon alpha [61]; ribavirin plus lopinavir-ritonavir plus interferon alpha versus lopinavir-ritonavir plus interferon alpha [61]; lincomycin versus azithromycin [62];, 99-mTc-methyl diphosphonate (99mTc-MDP) injection versus standard care [63]; interferon alpha-2b plus interferon gamma versus interferon alpha-2b [64]; telmisartan versus standard care [66]; avifavir 1800/800 versus avifavir 1600/600 [67]; dexamethasone plus aprepitant versus dexamethasone [69]; anti-C5a antibody versus standard care [70]; azvudine versus standard care [73]; human plasma-derived C1 esterase/kallikrein inhibitor versus standard care [72]; icatibant acetate versus standard care [72]; icatibant acetate versus human plasma-derived C1 esterase/kallikrein inhibitor [72]; pulmonary rehabilitation program versus isolation at home [71]; auxora (calcium release-activated calcium channel inhibitors) versus standard care [74]; umbilical cord stem cell infusion versus standard care [75]; vitamin C versus placebo [76]; sofosbuvir plus daclatasvir versus standard care [80]; sofosbuvir plus daclatasvir plus ribavirin versus hydroxychloroquine plus lopinavir-ritonavir with or without ribavirin [79]; interferon beta-1b versus standard care [81]; calcifediol versus standard care [84]; recombinant human granulocyte colony–stimulating factor versus standard care [85]; intravenous and/or nebulized electrolyzed saline w...…”
Section: Resultsmentioning
confidence: 99%
“…A small number of trials included in the present review reported on other types of therapies, including kinase or calcium release-activated calcium channel inhibitor, anticoagulants, convalescent plasma and other immunomodulatory or repair therapies [32,38,41,48,49,54,56]. Some studies showed either a significant efficacy effect or a trend towards improved efficacy [32,38,48,49,54,56]; however, in general the studies were of low quality and further clinical trials are required for a more conclusive demonstration of efficacy. In particular, although convalescent plasma has received emergency use authorisation from the US FDA, the decision was controversial, owing to a lack of robust supporting data [13].…”
Section: Discussionmentioning
confidence: 98%
“…Other therapies Trials (n=20-135) investigating the kinase inhibitor, ruxolitinib [32], the calcium release-activated calcium channel inhibitor, auxora [56], the anticoagulant, enoxaparin [54], and N-acetylcysteine, a mucolytic drug with anti-oxidant properties [49], in patients with severe COVID-19 reported no significant difference in mortality versus the comparator groups (figure 2c). One trial (n=200) reported a reduced 21-day mortality with recombinant human granulocyte colony-stimulating factor (rhG-CSF) added to standard care versus standard care alone (HR 0.19 (95% CI 0.04-0.88)) in patients with severe COVID-19 [48].…”
Section: Antimalarial and Mucolytic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In pilot studies, we have demonstrated that systemic chronic JPIII infusion for 28 days in mice did not induce any adverse effects, did not compromise the immune system, and did not promote susceptibility to develop infections ( Bartoli et al, 2020 ). Currently, no adverse effect has been reported in clinical trials with selective Orai1 inhibitors such as AnCoA4, CM2489, CM4620, and Auxora ( Stauderman, 2018 ; Miller et al, 2020 ). Nonetheless, given the important functional role of Orai1 in the immune system, it is important to properly understand the risks of potential adverse effects for a therapeutic approach moving forward.…”
Section: Pharmacological Opportunities Of Orai1 In Cardiac Diseasesmentioning
confidence: 99%